Special Investigative Techniques For Human Trafficking Investigation In Ethiopia - Negesse Asnake AYALEW (Indonesia Strategic Sustainability, 2020)
The police have the responsibility to balance public protection from harm by respecting the human rights of suspects during prevention and investigation. However, it is difficult to achieve absolute balance because it is determined based on the police because the process or model of crime control, especially in the case of special investigative techniques, is a confidential investigation of serious crimes based on the principles of legality, necessity, proportionality, and adequate protection. The purpose of the doctrinal article evaluates the role of special crime investigation techniques for human trafficking in Ethiopia. Data is collected through document review and interviews with crime investigators, intentionally and in direct contact. Qualitative research and descriptive design. The collected data is analyzed thematically. Research findings that there are some special investigative technical provisions in FDRE criminal justice policies, human trafficking and smuggling of migrant proclamations. However, this legal basis is not as comprehensive as specific types of investigation techniques, who did it and for how long, the requirements for doing this were not answered. Therefore, the House of Representatives must make a law covering all specific investigative techniques for human trafficking in Ethiopia. The Attorney General must also create public awareness about it.